Skiing is more than a parallel turn: high-level alpine ski racers talk about stressfull competitions in which they did and did not cope - Magelssen, C. (2012)
Within the world of elite alpine ski racing, there are numerous examples which show that skiers` ability to cope with competitive stress fluctuates. The overall aim of this thesis was to gain insight into why and what happens when high-level alpine ski racers cope with competitive stress and why and what happens when they do not. Moreover, to get insight into the factors which are associated positively and negatively with the ability to cope with competitive stress. Seven female Scandinavian high-level alpine ski racers (mean age = 18.6) participated in an Interpretative Phenomenological Analysis interview (IPA; Smith, Flowers & Larkin, 2009) regarding their `lived experiences` pertaining to one stressful competition in which they coped and one in which they did not cope. The skiers highlighted a long list of training and preparation variables, team variables and personal variables which affected their ability to cope positively and negatively in the respective competitions. Positive training and preparation variables included successful training sessions and/or races and meeting expectations, whereas tumbling into a technical, physical or psychological slump and not meeting expectations were seen as negative training and preparation variables. Positive team variables included feeling confident in the team, belonging to a high-ability team, having confidence in one`s team and receiving social support from the coach, whereas feeling the coach had lost faith in the skier, being exposed to overly controlling coaches and a lack of teammates` support were identified as negative variables. Finally, a large number of personal variables were identified in this study. The variables having a strong belief in success, possessing high relative competence, being task focused, having high perception of control and having an unwavering trust in one`s abilities were identified as positive personal variables. On the other hand, skiing beyond one`s capacity, possessing a high belief in failure, giving up, pushing too hard and exaggerated preparations were identified as negative variables. The results of this thesis are discussed in terms of the Cognitive Activation Theory of Stress (CATS; Eriksen & Ursin, 2006; Ursin & Eriksen, 2004) as well as a number of other relevant theories.